2000
DOI: 10.1017/s0958067000020509
|View full text |Cite
|
Sign up to set email alerts
|

Ageing modulates some aspects of the non-specific immune response of murine macrophages and lymphocytes

Abstract: The deterioration of the immune system with ageing, which leads to an increased morbidity and mortality from infections, appears to be related to decreases in specific lymphocyte functions. However, the alteration of non-specific immunity is a more controversial subject. Our purpose was to investigate the age-related changes of different functions of the non-specific immune response in peritoneal macrophages (adherence to tissues, mobility directed to a chemical gradient from an infectious focus or chemotaxis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…A significant decline in the adherence index was also observed in 16 mo old mice. Concurrent with our observation, Ortega et al (2000) observed a significant decline in adherence index during 22-48 weeks of age in female balb/c mice. The decline in adherence index of peritoneal macrophages with ageing could be because of decline in the ability of macrophages to form pseudopods (Johnson et al 1978), and decline in expression of various cell adhesion factors (ICAM-1 or VCAM-1) as reported in case neutrophils and monocytes of elderly (De Martinis et al 2004).…”
Section: Resultssupporting
confidence: 90%
“…A significant decline in the adherence index was also observed in 16 mo old mice. Concurrent with our observation, Ortega et al (2000) observed a significant decline in adherence index during 22-48 weeks of age in female balb/c mice. The decline in adherence index of peritoneal macrophages with ageing could be because of decline in the ability of macrophages to form pseudopods (Johnson et al 1978), and decline in expression of various cell adhesion factors (ICAM-1 or VCAM-1) as reported in case neutrophils and monocytes of elderly (De Martinis et al 2004).…”
Section: Resultssupporting
confidence: 90%
“…However, age does not affect all aspects of the immune response equally, since the influence of age on the non-specific immune response mechanism is not always negative. Thus, some studies suggest that the phagocytic cell functions do not change throughout life, while others have observed a senescent decrease or increase in them (Ortega et al, 2000). These different results have been attributed to an inappropriate choice of the age of the animals, which were considered old when really they were still not so.…”
Section: Ageing and The Immune Systemmentioning
confidence: 99%
“…These different results have been attributed to an inappropriate choice of the age of the animals, which were considered old when really they were still not so. Therefore, we have studied several immune functions of phagocytes (non-specific functions such as adherence, chemotaxis, ingestion and superoxide anion production as well as the production of proinflammatory cytokines TNF-a and IL-1b), of lymphocytes (adherence, chemotaxis, lymphoproliferations and IL-2 production) and NK activity in a range of ages in mice and humans (Ortega et al, 2000;De la Fuente & Victor, 2000;Guayerbas et al, 2002a,b). The changes of those functions with ageing are summarized in Table 1.…”
Section: Ageing and The Immune Systemmentioning
confidence: 99%
“…Aging is a very complex process that is related to circadian rhythm disruption and produces sleep disturbances (Huang et al 2002) and other physiological or psychological dysfunctions (Barnard and Nolan 2008) including impaired nutrient absorption (Meier and Sturm 2009;Woudstra and Thomson 2002), immunosenescence (Canizzo et al 2011;Hutt et al 2010;Ortega et al 2000), decrease in hormone levels (Ferrari and Magri 2008), or neuronal death (Shankar 2010;Qureshi and Parvez 2007). Adequate daily sleep is an important part of a healthy and productive lifestyle.…”
Section: Introductionmentioning
confidence: 99%